How can an infaunal brooding echinoid be maintained in the laboratory? A case study with Cassidulus mitis (Echinoidea: Cassiduloida) - Rezende-Ventura, Carlos-Renato (2021)
Introduction: Cassiduloids play a prominent role in echinoid evolutionary history because they probably are the ancestral group of clypeasteroids. Some extant species are brooding and rare in the environment. Consequently, there are no studies on their maintenance in the laboratory. Objective: Establish an efficient aquarium system for C. mitis, endemic to Brazil, for ontogenetic studies. Methods: Four aquarium systems were built, with 3 replicates each one: (1) with seawater flow [F]; (2) with seawater flow and air injection into sediment [FA]; (3) without seawater flow but with air injection into the sediment [A]; and (4) without both seawater flow and air injection into the sediment [C]. Each experimental aquarium (three per treatment) had two adults. Each of the two sets of experiments lasted about 60 days. Results: We observed low mortality in the first 30 days in all systems and, after 30 days, it was higher in those with air-pumped into the sediment (system A in the first set of experiments, and system FA in the second one). Conclusions: For experiments lasting 30 days, our four systems are suitable. For longer periods, we recommend aquaria with seawater flow and without air-pumps into the sediment.